(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines the role of intertextuality in Isajon Sultan’s "Azod" novels. The novel of the period of independence follows the path of artistic interpretation of the subject, human dreams and hopes, personal experiences, analysis of human psychology. The desire for self-realization is strong in artistic interpretations that have turned into essence. Isajon Sultan is one of our writers who strives to expand the scope of poetic thinking, to search for an answer to the question of what is the riddle of personality, and to realize that concepts are doomed to constant change